New hope or old futures in disguise? Neoliberalism, the Covid-19 pandemic and the possibility for social change. Issue 9 (22nd October 2020) - Briggs, Daniel; Ellis, Anthony; Lloyd, Anthony; Telford, Luke
Abstract : Purpose: The purpose of this paper is to consider the implications of both the Covid-19 pandemic and UK lockdown for the social, political and economic future of the UK. Drawing on primary data obtained during the lockdown and the theoretical concepts of transcendental materialism and the "event", the paper discusses the strength of participants' attachment to the "old normal" and their dreams of a "new normal". Design/methodology/approach: This paper utilises a semi-structured online survey ( n = 305) with UK residents and Facebook forum debates collected during the lockdown period in the UK. Findings: The findings in this paper suggest that while the lockdown suspended daily routines and provoked participants to reflect upon their consumption habits and the possibility of an alternative future, many of our respondents remained strongly attached to elements of pre-lockdown normality. Furthermore, the individual impetus for change was not matched by the structures and mechanisms holding up neoliberalism, as governments and commercial enterprises merely encouraged people to get back to the shops to spend. Originality/value: The original contribution of this paper is the strength and depth of empirical data into the Covid-19 pandemic, specifically the lockdown. Additionally, the synthesis of empirical data with the novel theoretical framework of transcendental materialism presents an original and unique perspective on Covid-19.